خطاب الالتزام وسماته الأسلوبية في ديوان خذني إلى المسجد الأقصى لأيمن العتوم - صوالح احميمة فتحي; عماري أحمد حسام; بوصوار فضل الله (University of El oued, 2025)
الأدب فن يلجأ إليه الإنسان للمتعة و المنفعة ، و حتى يكون نافعًا يجب عليه أن يحقق أهدافا نبيلة ، و الشاعر أيمن العتوم شاعر استطاع أن يوظف خطاب الالتزام في ديوانه ، فبرزت في ثنايا قصائده سمات أسلوبية قوية كالاختيار و الانزياح و التّناص ، و قد طبقها الشاعر بكيفيات راقية مكنته من أن يمرر رسائله بغية شحذ همم الشعوب العربية حتى تنهض لمساندة الشعب الفلسطيني حتى يستعيد حقوقه . Literature is an art that people resort to for pleasure and benefit , and in order for is to be useful , it must achieve noble goals . the poet AYMAN AL-ATOUM is a poet who was able to employ the discourse of commitment in his collection of poems , strong stylistic features such as choice , displacement , and deficiency emerged in the flods of his poems . the poet applied them in sophisticted ways that enabled him to justify his messages in order to galvanize the spirits of the arab peoples to that they rise up to support the palastinan people so that they can benefit from thier rights.
مذكرة .ماستر . أدب حديث ومعاصر2025
Keywords: الاختيار; الانزياح; التّناص; selection; displacement; intertextuality